ICT industries and smart cities: South Korea as technological link with Latin America - Bavoleo, Bárbara Inés (2020)
In recent years, South Korea has become a world benchmark in e-Government, ICT policies and Smart Cities, and has pursued a strong policy of assistance and consultation aimed especially at developing countries. In 2010, 2012 and 2014, South Korea ranked first in the world ranking of e-government carried out by the United Nations Public Administration Net-work (UNPAN). The country has managed to maximize the use of information and communications technologies in public administration to such an extent that practically any procedure can be carried out online.